Phylogeography of six codistributed New Zealand cicadas and their relationship to multiple biogeographical boundaries suggest a re‐evaluation of the Taupo Line. (26th May 2015) - Ellis, Emily A.; Marshall, David C.; Hill, Kathy B. R.; Owen, Christopher L.; Kamp, Peter J. J.; Simon, Chris
Abstract Aim Comparative biogeographers question the extent to which codistributed species respond similarly to environmental change. Such responses should create similar, appropriately timed patterns of cladogenesis among codistributed taxa compared to evolutionary independence, which may limit the predictions that can be made for unstudied species. Here, we compare phylogeographical patterns across ecologically divergent, codistributed taxa in the light of New Zealand's palaeohistory. Location North Island, New Zealand. Methods Mitochondrial DNA from six codistributed cicada species (Kikihia ochrina, K. cutora, K. laneorum, K. cauta, K. scutellaris and K. dugdalei) was analysed using phylogenetic methods and molecular dating techniques. We analysed phylogeographical distributions using analysis of molecular variance (AMOVA) to determine the significance of hypothesized biogeographical boundaries for clade differentiation and spatial distribution of genetic diversity. Results Five species (Kikihia ochrina, K. cutora, K. laneorum, K. cauta and K. scutellaris) show various degrees of intraspecific concordance with biogeographical boundaries found in previously studied taxa – the Kauri Line, the Northland Line and the newly identified Cockayne's Line. Clade splits of forest species correlate with the Kauri Line and/or Northland Line, whereas splits of scrub/hill species correlate with Cockayne's Line. Four species (Kikihia ochrina, K. cutora, K. laneorum and K. cauta) diversified before the Last Glacial Maximum (LGM, 20 ka), whereas two species (K. scutellaris and K. dugdalei) show only post‐LGM diversification. Main conclusions Despite species idiosyncrasies, we see the imprint of shared palaeoclimatic/geological events. We distinguish between (1) the importance of biogeographical lines as the demarcation between older genetically diverse and newer genetically depauperate populations, and (2) the importance of lines as biogeographical boundaries between sister clades. We also stress the importance of dating clade splits to ensure consistency with explanations for the biogeographical lines in question. We suggest that the Taupo Line has been overemphasized as a biogeographical boundary, whereas the importance of the mountain axis running north‐east to south‐west ('Cockayne's Line') has been overlooked.